Minimizing ice contamination during specimen preparation for cryo-soft X-ray tomography and cryo-electron tomography - Chia-Chun Hsieh; Zi-Jing Lin; Lee-Jene Lai (Journal of Structural Biology: X)
Cryo-soft X-ray tomography (cryo-SXT) is a newly developed technique for imaging 3D whole cells in nearly native states. Cryo-SXT users require the preparation of numerous cryo-sample grids to use the allocated beamtime to study cellular phenomena under various conditions. Therefore, it is important to promptly prepare cryo-sample grids as efficiently and carefully as possible to minimize ice contamination on the frozen sample grid. In this study, we designed a cryo-multi-grid-box storage system, which includes a shell, funnel holder, and multi-grid-box container. Our system not only increases the number of cryo-sample grids that can be temporarily stored but also reduces the frequency of cryo grid-box container transfers, thus decreasing the probability of forming ice on the grid. We have also applied this system to A549 cryo cell grid preparation. The correlative images from cryo-light microscopy and cryo-SXT showed that limited ice had formed on the grid when preparation was performed using our system. Additionally, 3D images of mitochondria with the lamellar shape of the cristae could be observed in our cryo-SXT results. Our cryo-multi-grid-box storage system can be used for cryo-SXT and cryo-electron tomography (cryo-ET) applications.